Recent Paramedic Graduates' Chronic Stress Adds Intentions to Leave the Profession: A Pilot Study Utilizing a Web-Based Survey - Anniina Herttuainen Master of Health Care, Bachelor of Emergency Care, RN; Hilla Nordquist PhD, MSc (Health) (SAGE Publishing, 2023)
Paramedics have mentally and physically demanding jobs, and chronic stress is not uncommon. Recently graduated paramedics, in particular, have been identified as needing support in their early careers. This pilot study examined chronic stress experienced by recent graduate paramedics and their intentions to leave the paramedic profession. Finnish paramedics encompass qualifications to work in various nursing sectors. This pilot study was a cross-sectional survey study among Finnish paramedics who graduated less than 3 years ago and who were currently working in prehospital EMS (n = 152). They evaluated chronic organizational and operational stressors on the Emergency Medical Services Chronic Stress Questionnaire with 20 statements. Two structured questions related to the intention to leave the paramedic profession. Three summary scales were formed. The differences in stress by the intention to leave were reported descriptively and the differences were tested with Mann-Whitney U test. The influence of potential predictors of the intention to leave prehospital EMS work or the nursing sector completely were explored with a forward stepwise logistic regression model. Those who intended to leave prehospital EMS work (25%, n = 35/152) or to leave the nursing sector completely (33%, n = 50/152) experienced higher levels of stress than those without such intentions. Stress related to organizational inequity and leadership challenges was the strongest and stress related to social, health, and personal impacts was the second strongest predictor of the intention to leave. Reducing chronic stress might be important in terms of paramedic retention. Several further study needs are addressed.